E-commerce taxation procedure : international and national standards - Makhmudov, Lazizbek (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Objective: controlled Kinsta the WordPress Hosting [1] According to the site, in 2017, e-commerce accounted for 3.26 percent ofglobal GDP, estimated at $ 2.3 trillion. It is expected that in 2021 this figure will double to 4.5 trillion. By 2040, 95% of total global sales is projected in the form of e-commerce. It can be seen that e-commerce is growing rapidly. Consequently, in the future it will be necessary to fully form and regulate this network infrastructure by the state. In this article, we want to present the results of our study on e-commerce taxation. Research Method: Empirical and theoretical methods were used in this article. The principles and rules of taxation developed by international organizations and various countries, including Uzbekistan, were studied, the impact of tax rates on electronic commerce in different countries on the development of the industry was calculated, and the tax regimes of different countries were compared. In the course of these studies, the method of analysis and synthesis of the theoretical method was used to analyze some specific cases, such as the impact of postal service prices on electronic commerce. In the final part, we formed our ideas using the method of induction and deduction and presented them in a single and complete review.The results of the study. Studies have shown that in the field of ecommerce taxation, there are a number of problems that are growingrapidly. First, tax rates must be set very carefully so that in the future there is motivation for the development of e-commerce; secondly, given the fact that e-commerce occurs on the Internet, it is necessary to determine the incentives for its taxation; thirdly, the fact that the tax rates imposed on electronic commerce are significantly different from regular trade rates is objectionable by other representatives of the industry, etc. In the final section, we described in detail our similar results. Research findings: In short, first of all, the countries of the world need to integrate with each other in collecting taxes on electronic commerce, otherwise there may be a legal basis for double taxation. In addition, if general taxation rules are not developed, tax revenues may be received by the other party. Since in some countries taxes are levied in the countries where they are consumed, in other countries they are taxed at the placewhere the seller is located